The Application of Environmental Management Accounting in Developing Sustainable Business Plans among Entrepreneurial Students of Politeknik Negeri Medan - Maya, Maya Syahlina; M. Rikwan Effendi Salam Manik; Indri Dithisari; Lisa Medina; Dewi Comala Sari (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to (1) identify the level of understanding of entrepreneurial students at Politeknik Negeri Medan regarding the principles of Environmental Management Accounting (EMA), (2) analyze the extent to which their business plans substantively reflect environmental aspects, and (3) formulate a conceptual model for implementing EMA as a foundation for sustainable entrepreneurship development.Method: This research adopts a descriptive qualitative approach through a case study design. Primary data were obtained from in-depth interviews with relevant participants and content analysis of the business plans they developed. The analysis focuses on exploring students’ perceptions, the challenges they encounter, and the environmental cost management components embedded in their planning.Results: The findings reveal a contradiction between the students’ strong commitment to ethics and sustainability and their limited technical competence in applying EMA to business planning contexts. Environmental aspects in their business documents are largely expressed qualitatively (such as environmentally friendly pledges) and have not yet integrated detailed calculations of environmental costs and eco-efficiency potential. This condition constrains the development of accountable business planning.Implications: These results highlight the critical need to revise the vocational education curriculum. Institutions should introduce practical EMA modules emphasizing environmental cost measurement so that Polmed graduates can design business plans that are not only ethical but also strategic and measurable from an accounting perspective.